2014
DOI: 10.1080/19443994.2014.969316
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of microcystin-LR by an amino acid-degrading anaerobic bacterium

Abstract: A B S T R A C TRecent studies have proved that microcystins (MCs) can be degraded by sediment under anaerobic conditions, suggesting that anaerobic biodegradation is an important pathway to remove MCs in water treatment. In this study, the potential for biodegradation of microcystin-LR (MCLR) by an amino acid-degrading anaerobic bacterium ALA-1 was investigated. Under mesophilic conditions (20, 25 and 30˚C), MCLR was dropped from 4 mg/L to below the detection limit in 10 d without lag phase. While at cold temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…YF3 with the maximum degradation rate of 0.34 mg/L/day under the optimal condition (37 • C, pH = 7, 5 mg/L MC-LR) [34]. Bao and Wu found that amino acid-degrading anaerobic bacterium ALA-1 had greater degrading ability under mesophilic and alkaline conditions than cold, neutral, and slightly acidic conditions [35]. Zhu et al deduced that Candidatus Cloacamonas acidaminovorans Evry may degrade MC-LR under anaerobic conditions through microbial community analysis [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YF3 with the maximum degradation rate of 0.34 mg/L/day under the optimal condition (37 • C, pH = 7, 5 mg/L MC-LR) [34]. Bao and Wu found that amino acid-degrading anaerobic bacterium ALA-1 had greater degrading ability under mesophilic and alkaline conditions than cold, neutral, and slightly acidic conditions [35]. Zhu et al deduced that Candidatus Cloacamonas acidaminovorans Evry may degrade MC-LR under anaerobic conditions through microbial community analysis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that MC-LR could be degraded by lake sediments under anoxic conditions with the production of final product Adda [25]. Linearized MC-LR, tetrapeptide, and adda, known as aerobic degradation products of MC-LR, were also produced by bacterium ALA-1 [35]. Two new linearized MC-LR, Ala-Leu-MeAsp-Arg-Adda-Glu-Mdha and Leu-MeAsp-Arg-Adda-Glu-Mdha-Ala, were detected in the degradation products of MC-LR, proving that new degradation pathways exit in anaerobic MC-degrading bacteria through hydrolyzing peptide bonds at Ala-Mdha and Ala-Leu [36,59].…”
Section: Discussionmentioning
confidence: 99%
“…However, the degradation rates of MCs were found to be higher under anaerobic conditions [ 76 ]. The degradation potential of the amino acid anaerobic strain ALA-1 for MC-LR was demonstrated by Bao et al This strain was able to degrade 4 mg/L MC-LR to levels below the detection limit within 10 days at moderate temperatures without a lag period [ 77 ]. An analysis of MCs in cyanobacterial cells and the biodegradation of MC-YR, -RR, and -LR by Sphingomonas sp.…”
Section: Biodegradationmentioning
confidence: 99%
“…The genetic and enzymatic mechanism of the Microcystinase (Mlr)-dependent pathway for MC biodegradation was fully described, in which MC is degraded sequentially into linearized MC, tetrapeptides, Adda, phenylacetic acid, and ultimately, CO 2 , via a series of specific enzymes encoded by mlr and neighboring paa gene clusters [ 25 , 26 , 27 ]. The mlr -dependent degradative activity of indigenous bacteria is under strict control and is affected by multiple factors [ 28 , 29 , 30 ]. Therefore, the direct modulation of wild MC-degraders in practical applications remains a challenge.…”
Section: Introductionmentioning
confidence: 99%